2017
DOI: 10.1111/risa.12929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Distribution of Animals between Dose Groups on Estimated Benchmark Dose and Animal Welfare for Continuous Effects

Abstract: The benchmark dose (BMD) approach is increasingly used as a preferred approach for doseeffect analysis, but standard experimental designs are generally not optimized for BMD analysis. The aim of this study was to evaluate how the use of unequally sized dose groups affects the quality of BMD estimates in toxicity testing, with special consideration of the total burden of animal distress. We generated continuous dose-effect data by Monte Carlo simulation using two dose-effect curves based on endpoints with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The rest of the doses should be spread over the resulting dose scale. More generally, it has repeatedly been shown to be advantageous to have studies with one or more doses near the level of the true BMD (Piegorsch et al., ; Ringblom, Kalantari, Johanson, & Öberg, ; U.S. EPA, ). Obviously, these suggestions require some prior data to be practically applied.…”
Section: Additional Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rest of the doses should be spread over the resulting dose scale. More generally, it has repeatedly been shown to be advantageous to have studies with one or more doses near the level of the true BMD (Piegorsch et al., ; Ringblom, Kalantari, Johanson, & Öberg, ; U.S. EPA, ). Obviously, these suggestions require some prior data to be practically applied.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Although pairwise comparison strategies, such as NOAEL and the lowest adverse effect level (LOAEL), benefit from designs with equal group sizes, this is not necessarily the case for the BMD approach (Öberg, ). In the context of animal experiments, two recent studies (Ringblom et al., ) showed that varying the number of animals used between doses while retaining the same number of doses may reduce animal stress without changing the precision of the estimated BMD. A similar finding was reported by Shao and Small (), who found only a limited effect on BMD precision by unbalanced designs, but a tendency toward increased precision by placing more animals in the lower dose groups and fewer in the higher dose groups, resulting in higher animal welfare (Öberg, ).…”
Section: Additional Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most publications about the BMD approach focus on the mathematical/statistical aspects of modeling 27 and the study design effects such as group sizes. 28 In this study, we want to critically discuss BMD modeling in the context of potentially different MOAs associated with different subpopulations inadvertently included in the study contributing to the observed total response of interest.…”
Section: Introductionmentioning
confidence: 99%